Keefektifan Hubungan Tingkat Profitabilitas Perusahaan terhadap Harga Saham - Setyo Liyundira, Fetri (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Effectiveness of the Relationship Level of the Company's Profitability to Stock Prices. The capital market becomes and has a major economic function in the Indonesian economy, two parties, namely investors and publishers who provide several things facilitated by the capital market that provides facilities or vehicles. Profitability ratios used are indicators of Return On Investment (ROI) and Earnings Per Share (EPS) to stock prices. The sample used was 56 companies that have entered into several criteria and then submitted an application using SPPS with classic approval issued first for all variables, after collecting classic assumptions then performed a statistical test to determine the relationship of cause and effect. The results of the statistical test can be concluded that investors consider various things and one of them is looking at the value of Return on Investment (ROI). Profit will be generated by the use of increased company assets so that the value of the company can be increased, in accordance with rising stock prices to get a good response from investors. In addition to the profits generated, investors also benefit investors. It is wrong to only see profits because big or small will show the company's ability to distribute dividends to investors. From this it appears that a complicated transaction occurs, investors will receive dividends will be higher, it is seen getting a company.